Effect of an estetrol/drospirenone contraceptive on sexual function in women of reproductive age - Mekan R. Orazov; Vasily V. Ermakov; Dmitrii S. Novginov (IP Berlin A.V., 2023)
The use of hormonal contraception is widespread worldwide. Over the years of use, it has been possible to study its contraceptive effectiveness and its effect on carbohydrate metabolism, blood coagulation, lipid profile, liver function tests, and other systems and organs. However, the effect on sexual function has not been sufficiently studied. For a long time, ethinylestradiol remained the main estrogen in combined oral contraceptives; however, the desire to improve safety led to the development of a new drug containing natural, highly selective estrogen estetrol and the well-known progestogen drospirenone. Therefore, it is relevant to study the effect of the new combined oral contraceptive on sexual function.